Implementasi Kebijakan Otonomi Desa Berdasarkan Hak Asal Usul Desa Dan Kewenangan Lokal Berskala Desa di Desa Tideng Pale Kecamatan Sesayap Kabupaten Tana Tidung - Asriani; Ibnu Sabil; Rahmat Hidayat (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The enactment of Law No. 6 of 2014 on Villages has influenced a more comprehensive regulation of village authority. This village authority encompasses powers derived from tradition and also local authority at the village level, both of which are at the core of village autonomy. This research adopts the Legal Science Research method with the support of social sciences, emphasizing the concept that law is not merely a set of normative rules but also an integral part of community life. In Tideng Pale Village, Sesayap District, Tana Tidung Regency, the implementation of ancestral authority, as regulated by Law No. 6 of 2014 on Villages, has not been fully carried out because this authority does not yet exist, thus, it only includes the resolution of land disputes based on tradition and customary marriages. Meanwhile, local authority at the village level is realized through the preparation of the Village Revenue and Expenditure Budget (APBDesa), reflected in the List of Activity Plans (DRK), which is adjusted annually in accordance with the amount of APBDesa.